2010
DOI: 10.1007/s00441-010-1014-4
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of skin antimicrobial peptides to the system of innate immunity in anurans

Abstract: Cationic peptides with the propensity to adopt an amphipathic α-helical conformation in a membrane-mimetic environment are synthesized in the skins of many species of anurans (frogs and toads). These peptides frequently display cytolytic activities against a range of pathogenic bacteria and fungi consistent with the idea that they play a role in the host's system of innate immunity. However, the importance of the peptides in the survival strategy of the animal is not clearly understood. It is a common misconce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
103
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(109 citation statements)
references
References 106 publications
2
103
0
3
Order By: Relevance
“…cuticular exoskeleton or shell) to physically protect their underlying tissues from direct biotic/abiotic interactions are particularly suited to studying the adaptation of external immunity to changing and harsh environmental conditions. Rather than physical protection, annelids have developed a strong external immunity based on the production of mucus and AMPs by the epidermic cells that respectively trap and kill/select pathogenic/symbiotic bacteria (Salzet et al 2006;Tasiemski and Salzet 2010;Conlon 2011;Gallo and Nakatsuji 2011). For instance, polychaetes produce original AMPs, some of which are restricted to just one worm family (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…cuticular exoskeleton or shell) to physically protect their underlying tissues from direct biotic/abiotic interactions are particularly suited to studying the adaptation of external immunity to changing and harsh environmental conditions. Rather than physical protection, annelids have developed a strong external immunity based on the production of mucus and AMPs by the epidermic cells that respectively trap and kill/select pathogenic/symbiotic bacteria (Salzet et al 2006;Tasiemski and Salzet 2010;Conlon 2011;Gallo and Nakatsuji 2011). For instance, polychaetes produce original AMPs, some of which are restricted to just one worm family (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our methods for chemical analysis (reverse-phase LCMS) have been optimized for observation of bacterial metabolites [36]. Many known metabolites of amphibian origin that inhibit pathogens and provide defence against predators, such as antimicrobial peptides [62] and zetekitoxin [63], respectively, are too polar to be observed in our conditions. Antimicrobial peptides have not been detected in captive A. zeteki (B. Sheafor 2014, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiotic microbes can therefore be regarded as another component of amphibians' innate immune defence mechanisms (Woodhams et al 2007b, Walke et al 2011. Symbiotic bacteria resident on anuran skin may sometimes play a greater role than AMPs in defence against Bd, and AMP potency may be attenuated in species that rely heavily on their beneficial microbiota (Conlon 2011). Harris et al (2006) first demonstrated in vitro inhibition of Bd by a number of bacterial species isolated from the skin of salamanders, and suggested that Bdinhibiting bacteria could be used as a bioaugmentation tool to confer disease resistance to vulnerable amphibian populations.…”
Section: Introductionmentioning
confidence: 99%